Autoimmune Cytopenias in Common Variable Immunodeficiency Are a Diagnostic and Therapeutic Conundrum: An Update - Chawla, Sanchi; Barman, Prabal; Tyagi, Rahul; Jindal, Ankur Kumar; Sharma, Saniya; Rawat, Amit; Singh, Surjit (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID) is the most common symptomatic primary immunodeficiency (PID). CVID is a heterogenous condition and clinical manifestations may vary from increased susceptibility to infections to autoimmune manifestations, granulomatous disease, polyclonal lymphoproliferation, and increased risk of malignancy. Autoimmune manifestations may, at times, be the first and only clinical presentation of CVID, resulting in diagnostic dilemma for the treating physician. Autoimmune cytopenias (autoimmune haemolytic anaemia and/or thrombocytopenia) are the most common autoimmune complications seen in patients with CVID. Laboratory investigations such as antinuclear antibodies, direct Coomb’s test and anti-platelet antibodies may not be useful in patients with CVID because of lack of specific antibody response. Moreover, presence of autoimmune cytopenias may pose a significant therapeutic challenge as use of immunosuppressive agents can be contentious in these circumstances. It has been suggested that serum immunoglobulins must be checked in all patients presenting with autoimmune cytopenia such as immune thrombocytopenia or autoimmune haemolytic anaemia. It has been observed that patients with CVID and autoimmune cytopenias have a different clinical and immunological profile as compared to patients with CVID who do not have an autoimmune footprint. Monogenic defects have been identified in 10-50% of all patients with CVID depending upon the population studied. Monogenic defects are more likely to be identified in patients with CVID with autoimmune complications. Common genetic defects that may lead to CVID with an autoimmune phenotype include nuclear factor kappa B subunit 1 (NF-kB1), Lipopolysaccharide (LPS)-responsive beige-like anchor protein (LRBA), cytotoxic T lymphocyte antigen 4 (CTLA4), Phosphoinositide 3-kinase (PI3K), inducible T-cell costimulatory (ICOS), IKAROS and interferon regulatory factor-2 binding protein 2 (IRF2BP2). In this review, we update on recent advances in pathophysiology and management of CVID with autoimmune cytopenias.